Kaonic atoms at the DAΦNE collider: a strangeness adventure - Curceanu, C.; Abbene, L.; Amsler, C.; Bazzi, M.; Bettelli, M.; Borghi, G.; Bosnar, D.; Bragadireanu, M.; Buttacavoli, A.; Cargnelli, M.; Carminati, M.; Clozza, A.; et al. (Frontiers in Physics, 2023)
Kaonic atoms are an extremely efficient tool to investigate the strong interaction at the low energy frontier, since they provide direct access to the K − N interaction at threshold, eliminating 1 C. Curceanu, et al.the necessity for extrapolation, unlike in the case of scattering experiments. During the 1970s and 1980s, extensive studies were performed on kaonic atoms spanning across a broad spectrum of elements in the periodic table, ranging from lithium to uranium. These measurements provided inputs and constraints for the theoretical description of the antikaon-nuclei interaction potential. Nevertheless, the existing data suffer from significant experimental uncertainties, and numerous measurements have been found to be inconsistent with more recent measurements that utilize advanced detector technology. Furthermore, there remain numerous transitions of kaonic atoms that have yet to be measured. For these reasons, a new era of kaonic atoms studies is mandatory.The DAΦNE electron-positron collider at the INFN Laboratory of Frascati (INFN-LNF) stands out as a unique source of low-energy kaons, having been utilized by Collaborations such as DEAR, SIDDHARTA, and AMADEUS for groundbreaking measurements of kaonic atoms and kaon-nuclei interactions. Presently, the SIDDHARTA-2 experiment is installed at DAΦNE, aiming to perform the first-ever measurement of the 2p → 1s x-ray transition in kaonic deuterium, a crucial step towards determining the isospin-dependent antikaon-nucleon scattering lengths.Based on the experience gained with the SIDDHARTA experiment, which performed the most precise measurement of the kaonic hydrogen 2p → 1s x-ray transition, the SIDDHARTA-2 setup is now fully equipped for the challenging kaonic deuterium measurement. In this paper, we present a comprehensive description of the SIDDHARTA-2 setup and of the first kaonic atoms measurements performed during the commissioning phase of the DAΦNE collider. We also outline a proposal for future measurements of kaonic atoms at DAΦNE beyond SIDDHARTA-2, which is intended to stimulate discussions within the broad scientific community performing research, directly or indirectly, related to this field.